Economic valuation of the Danau Sentarum National Park, West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Authors. 2019. Economic valuation of the Danau Sentarum National Park, West Kalimantan, Indonesia. Biodiversitas 20: 1983-1989. The Danau Sentarum ecosystem in West Kalimantan, Indonesia is officially protected by its status as an Indonesian national park. Nevertheless, it remains under severe threat of deforestation. Rainforest destruction has already caused a decline in ecosystem functions and services. In addition, it is affecting numerous economic activities in and around the Danau Sentarum National Park. The objectives of this study are to determine the total economic value (TEV) of the Danau Sentarum National Park and look for appropriate mechanisms to realize such values. Survey methods were used in this research. 180 respondents were selected by random sampling method from three Management Section National Park (MSNP). TEV in this research was restricted on direct use value, indirect use value and option value. Estimation of DSNP ecosystem benefits was approached by market price, travel cost method, contingent valuation method, and opportunity cost adjusted for the benefits calculated. The direct use value of Danau Sentarum National Park is IDR 18.5 billion/year while the indirect use value of Danau Sentarum National Park is IDR 34.2 billion/year. The option value of Danau Sentarum National park is IDR 86.2 billion/year. The total economic value resulted in Danau Sentarum National Park is IDR 139,1 billion/year, equivalent to an average of IDR 1.1 million/year for the total park area (132,000 ha). When compared to the TEV of the DSNP, such costs amounted to only 4.87 percent compared to the value of the benefits Based on monetary values of ecosystem services that are provided by this park we could assess the mechanisms to finance the park’s conservation and sustainable use. This will help the self-management of national parks.
Keywords: valuation, ecosystem services, total economic value, management, national parks